Deregulated methylation and expression of PCDHGB7 in patients with non-small cell lung cancer: a novel prognostic and immunological biomarker - Yuan, Yue; Nie, Xin; Gao, Jiayi; Tian, Yumeng; He, Liuer; Wang, Xue; Zhang, Ping; Ma, Junling; Li, Lin (Frontiers in Immunology, 2025)
BackgroundsProtocadherin gamma subfamily B, 7 (PCDHGB7), a member of the protocadherin family, plays critical roles in neuronal connections and has been implicated in female reproductive system cancers. Its function in lung cancer has not been elucidated.MethodsWe comprehensively investigated PCDHGB7 expression, prognosis, biological function, methylation patterns, and it’s relationship with immune infiltration and immunotherapy response through public datasets (HPA, TCGA, GEO, OncoDB and MEXPRESS). Two lung cancer immunotherapy cohorts from our clinical center were enrolled to detect the relationship between methylation and protein levels of PCDHGB7 in plasma and immunotherapy outcomes.ResultsPCDHGB7 expression was downregulated in lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) and associated with tumor prognosis. PCDHGB7 demonstrated a positive correlation with inhibitory immune cells and a negative correlation with tumor mutational burden (TMB) and homologous recombination deficiency (HRD). The methylation level of PCDHGB7 was upregulated in tumor tissue and negatively correlated with PCDHGB7 mRNA level. In immunotherapy cohort studies, patients with higher PCDHGB7 tissue expression showed worse prognosis. Patients with PCDHGB7 hypermethylation in baseline plasma had shorter progression-free survival (PFS) and overall survival (OS), while those with early reduction of PCDHGB7 methylation had the best prognosis. Plasma PCDHGB7 protein levels could predict responses to immune checkpoint inhibitors and function as a prognostic marker for PFS.ConclusionPCDHGB7 expression and methylation are prognostic and immunological biomarkers in non-small cell lung cancer. Plasma PCDHGB7 methylation and protein levels can be used as novel biomarkers for predicting the efficacy of immunotherapy in lung cancer.